Uji Ketahanan Penyakit Antraknosa pada Tanaman Cabai (Capsicum annuum L.) Hibrida IPB di Dataran Rendah Karawang - Simbolon, Dedy Ricardo; Syafi’i, Muhammad; Syukur, Muhammad (JURNAL AGROPLASMA, 2023)
The necessity of chili (Capsicum annuum L.) increases highly in line with the enhancement of residents and the food industry development that need chili ingredients. It affects the commodity to become an often-discussed commodity in society because its price can increase highly in certain conditions. The study aimed to obtain the resistance of anthracnose disease to ten varieties of chili (Capsicum annuum L.) hybrid IPB in Karawang lower altitudes. The research was conducted in Trial Field of Peruri, Teluk Jambe Sub-district, Karawang District, Jawa Barat from February to July 2022. The research used the randomized complete group design (RKLT) method with 3 replications. There are 10 treatments such as A (F1074005), B (F1074003), C (F1374005), D (F1374003), E (CH3), F (BAJA), G (BALEBAT), H (ELEGANCE), I (IMPERIAL 10), dan J (GADA). Treatment factor was analyzed with variety analysis and if F test at  5%  level was significant, then continued DMRT test at 5% level to find out the best treatments. Treatment I (IMPERIAL 10) had highest result on fruit length and fruit stalk length and was highly resistant to anthracnose disease. Treatment C (Genotype F1374005) had highest result on fruit weight and was highly resistant to anthracnose disease. Keywords: anthracnose, chili, genotype